Peripheral eosinophil trends and clinical outcomes after non-traumatic subarachnoid hemorrhage - Gonzalez Gomez, Hugo; Savarraj, Jude P. J.; Paz, Atzhiry S.; Ren, Xuefang; Chen, Hua; McCullough, Louise D.; Choi, Huimahn A.; Gusdon, Aaron M. (Frontiers in Neurology, 2023)
Background/Objective: Uncontrolled systemic inflammation after non-traumatic subarachnoid hemorrhage (SAH) is associated with worse outcomes. Changes in peripheral eosinophil count have been linked to worse clinical outcomes after ischemic stroke, intracerebral hemorrhage, and traumatic brain injury. We aimed to investigate the association of eosinophil counts with clinical outcomes after SAH. Methods: This retrospective observational study included SAH patients admitted from January 2009 to July 2016. Variables included demographics, modified FS (mFS), Hunt Hess Scale (HHS), Global Cerebral Edema (GCE), and presence of any infection. Peripheral eosinophil counts were examined as part of routine clinical care on admission and daily for 10 days after aneurysmal rupture. Outcome measures included dichotomized discharge mortality, modified Ranked Scale (mRS) score, delayed cerebral ischemia (DCI), vasospasm, and need for ventriculoperitoneal shunt (VPS). Statistical tests included Chi-square test, student’s t-test and multivariable logistic regression (MLR) models. Results: A total of 451 patients were included. Median age was 54 years (IQR 45, 63) and 295 (65.4%) were female. On admission, 95 (21.1%) had a high HHS (>4), and 54 (12.0%) had GCE. 110 (24.4%) of the patients had angiographic vasospasm, 88 (19.5%) developed DCI, 126 (27.9%) had an infection during hospitalization, and 56 (12.4%) required VPS. Eosinophil counts increased and peaked at days 8-10. Higher eosinophil counts on days 3-5 and days 8 were seen in patients with GCE (p<0.05). Higher eosinophil counts on days 7-9 (p<0.05) occurred in patients with poor discharge functional outcomes. In multivariable logistic regression models, higher day 8 eosinophil count was independently associated with worse discharge mRS (OR 6.72 [95%CI 1.27, 40.4], p=0.03). Conclusions: This study demonstrated that a delayed increase in eosinophils after SAH occurs and may contribute to functional outcomes. The mechanism of this effect as well as the relationship with SAH pathophysiology merit further investigation.